Crustal‐scale block tilting during Andean trench‐parallel extension: Structural and geo‐thermochronological insights. Issue 9 (17th September 2016) - Noury, M.; Bernet, M.; Schildgen, T. F.; Simon‐Labric, T.; Philippon, M.; Sempere, T.
Abstract: Despite a long history of plate convergence at the western margin of the South American plate that has been ongoing since at least the Early Paleozoic, the southern Peruvian fore‐arc displays little to no evidence of shortening. In the light of this observation, we assess the deformation history of the southern Peruvian fore‐arc and its geodynamic implications. To accomplish this, we present a new structural and geo‐thermochronological data set (zircon U‐Pb, mica 40 Ar/ 39 Ar, apatite and zircon fission‐track and zircon (U‐Th)/He analyses) for samples collected along a 400 km long transect parallel to the trench. Our results show that the Mesoproterozoic gneissic basement was mainly at temperatures ≤350°C since the Neoproterozoic and was later intruded by Jurassic volcanic arc plutons. Along the coast, a peculiar apatite fission‐track age pattern, coupled with field observations and a synthesis of available geological maps, allows us to identify crustal‐scale tilted blocks that span the coastal Peruvian fore‐arc. These blocks, bounded by normal faults that are orthogonal to the trench, suggest post‐60 Ma trench‐parallel extension that potentially accommodated oroclinal bending in this region. Block tilting is consistent with the observed and previously described switch in the location of sedimentary sources in the fore‐arc basin. Our data set allows us to estimate the cumulative slip on these faults to be less than 2 km and questions the large amount of trench‐parallel extension suggested to have accommodated this bending. Key Points: New geo‐thermochronological data set along a 400 km long trench‐parallel profile Southern Peruvian fore‐arc deformation history and its linkage to oroclinal bending Crustal‐scale block tilting occurs contemporaneously to oroclinal bending